Modifikasi Pembelajaran Ekspository Learning dengan Media Kartu untuk Membelajarkan Materi Pecahan bagi Siswa SD - Suryani, Lilis; Jelita; Rahayu, Nina (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2021)
One of the efforts that teachers can make to improve student learning achievement is to manipulate learning strategies and teaching media. So this research, will be used expository learning strategies and card media to align fractional material for students of class V. The purpose of this study is to describe learning outcomes in fractional material by using exposure learning strategies and card media. The research was conducted at SD Negeri 050783 Salahaji, Langkat Regency. This type of research is action research with the design of Kurt Lewin. The study was conducted on 24 class V students. Research instruments in the form of a description test numbering 5 questions. Based on the results of research obtained the average completion of learning in cycle I is 46.39 (45.83%) with the number of completed students as many as 11 people and 69.6 (79.2%) in cycle II with the number of completed students as many as 19 people. Thus it is concluded that the use of fractional card media with strategi expository learning can improve learning outcomes in fractional material